Mapping the Potential of Conflict Between Villages in the Bima District - Ahmad, Syarif; Khaldun, Ibnu; Basri, Seta; Chumaedi, Ahmad (Universitas Muhammadiyah Tangerang, 2023)
This study aims to determine the map of potential inter-village conflicts, identify various factors triggering inter-village conflicts and formulate strategies for handling inter-village conflicts that occur in Bima Regency, West Nusa Tenggara Province. To answer research problems, qualitative methods with descriptive analysis are used, while case studies are used to limit this study to the specificity of certain characteristics and limitations of certain areas. Bima Regency consists of 18 sub-districts where conflicts between villages have the potential to occur in 5 sub-districts, namely; Woha sub-district, Monta sub-district, Belo sub-district, Bolo sub-district and Sape sub-district. The trigger factors for conflict include the abuse of narcotics and drugs (drugs), liquor (Miras), and differences of understanding between individual citizens. The actors involved in inter-village conflicts are educated college graduates who are unemployed and village elites who lose in contesting the Village Head election. Penelitian ini bertujuan untuk mengetahui peta potensi konflik antarkampung, mengidentifikasi berbagai faktor pemicu terjadinya konflik antarkampung dan perumusan strategi penanganan konflik antarkampung yang terjadi di Kabupaten Bima Provinsi Nusa Tenggara Barat. Untuk menjawab permasalahan penelitian, digunakan metode kualitatif dengan analisis deskriptif, sementara studi kasus digunakan untuk membatasi studi ini pada kekhususan karakteristik dan keterbatasan wilayah tertentu. Kabupaten Bima terdiri dari 18 Kecamatan di mana konflik antar kampung berpotensi terjadi terjadi pada 5 Kecamatan, yaitu; Kecamatan Woha, Kecamatan Monta, Kecamatan Belo, Kecamatan Bolo dan Kecamatan Sape. Faktor-faktor pemicu terjadinya konflik antara lain yakni dipicu oleh penyalahgunaan narkotika dan obat-obatan (Narkoba), minuman keras (Miras), dan selisih paham antar individu warga. Adapun para aktor yang ikut terlibat dalam konflik antarkampung yaitu kaum terdidik lulusan Perguruan Tinggi yang menganggur dan elit-elit desa yang kalah dalam kontestasi pemilihan Kepala Desa.